Excess Risk of Tuberculosis Infection Among Extra-household Contacts of Tuberculosis Cases in an African City. (16th October 2020) - Kakaire, Robert; Kiwanuka, Noah; Zalwango, Sarah; Sekandi, Juliet N; Quach, Trang Ho Thu; Castellanos, Maria Eugenia; Quinn, Frederick; Whalen, Christopher C
Abstract: Background: Although households of tuberculosis (TB) cases represent a setting for intense transmission of Mycobacterium tuberculosis, household exposure accounts for <20% of transmission within a community. The aim of this study was to estimate excess risk of M. tuberculosis infection among household and extra-household contacts of index cases. Methods: We performed a cross-sectional study in Kampala, Uganda, to delineate social networks of TB cases and matched controls without TB. We estimated the age-stratified prevalence difference of TB infection between case and control networks, partitioned as household and extra-household contacts. Results: We enrolled 123 index cases, 124 index controls, and 2415 first-degree network contacts. The prevalence of infection was highest among household contacts of cases (61.5%), lowest among household contacts of controls (25.2%), and intermediary among extra-household TB contacts (44.9%) and extra-household control contacts (41.2%). The age-adjusted prevalence difference between extra-household contacts of cases and their controls was 5.4%. The prevalence of infection was similar among the majority of extra-household case contacts and corresponding controls (47%). Conclusions: Most first-degree social network members of TB cases do not have adequate contact with the index case to experience additional risk for infection, but appear instead to acquire infection through unrecognized exposures with infectious cases in the community. Abstract : Most first-degree social network members of tuberculosis cases do not have adequate contact with the index case to experience additional risk for infection, but appear to acquire infection through exposures with infectious cases in unrecognized contact networks in the community.